Comparative Pharmacology of Direct Oral Anticoagulants and Vitamin K Antagonist - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
Background: The prevalence of thrombus and use of anticoagulants is routine in clinical cardiology practice. Vitamin K antagonist (VKA) and/or Direct oral anticoagulants (DOAC) are used for resolution of the thrombus. Despite similar anticoagulation efficacy, use of DOAC is preferred due to their superior safety margin and reduced risk of bleeding. Currently the following DOAC are available for the prevention of thrombosis, i.e., dabigatran, rivaroxaban, apixaban, edoxaban, and betrixaban. This study evaluates the comparative pharmacology of these DOAC and VKA to assess clinical preference. Materials and Methods: The human specific targets of DOAC and VKA (Warfarin) were identified from the SwissTargetPrediction server and analysed for their affinity. The targets were subclassified into functional categories and the relative proportion of each of the functional categories among the total number of targets was estimated. A novel concentration affinity (CA) ratio system was developed for the drugs to assess their safety margin and compared. Results: The following targets were identified has high affinity targets of DOAC or VKA i.e., coagulation factor X, hERG, matriptase, multidrug and toxin extrusion protein 1, plasminogen, quinone reductase 1 and 2, serine protease hepsin, solute carrier family 22 member 2 and thrombin. Apixaban and rivaroxaban were observed to have superior anticoagulation pharmacology compared to the other DOAC or VKA. Edoxaban and betrixaban were observed to have affinity against hERG, which carries the risk of prolonging QT interval and triggering ventricular tachyarrhythmia. Conclusion: This study shows the comparative pharmacology of DOAC and VKA and suggests preferential use of apixaban or rivaroxaban due to their superior pharmacodynamic effects and wider safety margin.
Keywords: Cardiovascular; Myocardial infarction; Thrombosis; Clot; Anticoagulant